Surface modification of polymer by ion assisted reaction - Koh, S.K.; Choi, S.C.; Han, S.; Cho, J.; Choi, W.K.; Jung, H.-J.; Hur, H.H. (1998)
Wettable surface of polymers (advanced wetting angle ∼10° and surface energy ∼ 60 - 70 erg/cm2) have been accomplished by the ion assisted reaction, in which energetic ions are irradiated on polymer with blowing oxygen gas. The energies of ions are varied from 0.5 to 1.5 keV, doses 1014 to 1017 ions/cm2, and blowing rate of oxygen 0 ∼ 8 ml/min. The wetting angles are increased when the wettable polymers were exposed in air, but are remained in pure water. Improvement of surface energy is mainly due to the polar force surface analysis shows hydrophilic functional groups such as C=O, (C=O)-O, C-O, etc., are formed without surface damage after the ion assisted reaction treatment. Comparisons between the conventional surface treatments and the ion assisted reaction are described in term of physical bombardment, surface damage, functional group, and chain mobility in polymer. ？ 1998 Trans Tech Publications.
Keywords: Chemical modification; Interfacial energy; Ion bombardment; Surface treatment; Wetting; Hydrophilic functional groups; Polymer chain mobility; Polymers